Behavioral Assessment of Children as Active Social Media Users in the Generation Alpha Environment: The Moderating Role of Teacher and Parent Supervision - Dessy Rahma Ardian Nufus; Wahyudi Sujadmiko (AGUSPATI Research Institute, 2026)
This study aims to assess the influence of social media use on children's behavioral deviation in the Generation Alpha (Gen Alpha) environment and to examine the moderating effects of teacher and parent supervision. Utilizing a mixed-methods approach with an explanatory sequential design, quantitative data were obtained through Likert-scale questionnaires and a Situational Judgment Test (SJT). Qualitative data were gathered through clinical observations and in-depth interviews at SDN Pati Wetan 01 (p. 1). The results of the analysis using Moderated Regression Analysis (MRA) prove that the intensity of social media use has a significant effect on the behavioral changes of Gen Alpha. This phenomenon manifests in attention span deficits, verbal degradation based on cyber slang, cyber clustering, and fragile emotional regulation (withdrawal syndrome). The moderation regression test indicates that parental and teacher supervision acts as a pure moderator that weakens these negative impacts. However, a wide regulatory gap was found between restrictive supervision at school and permissive parenting at home due to parents' limited digital literacy. This study recommends a parallel synergy model through integrated digital parenting programs to safeguard the morality of Generation Alpha.